Functional physical fitness in elderly: diferences depending on the practice of physical activity - Silveira, Paulo (2019)
This study aims to verify the impact of physical activity on the physical fitness of elderly. The sample consisted of 348 elderly individuals aged between 61 and 97 years, divided into 2 groups (254 practitioners of Physical Activity and 94 non-practitioners). From the first group 48 practice hydrogymnastics and 206 practice gymnastics. Physical fitness was assessed following the test protocol of the Senior Fitness Test battery (Rikli & Jones, 2001). In addition to descriptive statistics, the Kolmogorov Smirnov, Mann-Whitney and Kruskal Wallis statistical tests were used with comparisons by pairs. The results allowed to identify that in each and every one of the tests of functional physical fitness there are statistically differences between practitioners and non- practitioners of PA, with mean averages significantly higher by the practitioners. The practice of any of these activities (Hydrogymnastics and Gymnastics) reveals significant differences with the group of non-practitioners, and the means obtained in any of the physical fitness tests of the two groups of practice much superiors compared to the non- practitioners. There are also significant differences between Hydogymnastic and Gymnastics practitioners in the test sitting, walking 2.44 m and sitting again, and walking for 6 minutes, where the gymnastic practitioners obtained better results in both tests.